La Prédiction Du Potentiel D’Intervention De Futurs Conseillers: Un Processus En Réévaluation Continuelle - Cyr, Mireille; Lecomte, Conrad; Perron, Jacques; Alain, Michèle (Canadian Journal of Counselling and Psychotherapy, 2011)
Prediction of therapeutic potential in aspiring counsellors is a crucial issue each year at the time of the graduate admissions process. In the present study, the performance of 46 graduate student applicants in two roleplay sessions was evaluated by two independent judges. Measures of the applicant expectancies regarding their own behaviour as therapists, cognitive complexity, inferential skills, communicational skills as well as academic achievement, age, and previous counselling experience were used as predictors of performance. Multiple regression analyses revealed that only the differentiation score (one of the inferential skills measured) was moderately predictive of the global judgement made by the observers. In addition, although interobserver agreement increased over ratings, the highest level of agreement between judges was only moderate. Problems related to the prediction of success in a counseling situation are discussed and some procedural improvements are suggested for future research.